The socioeconomic impact of seismic events on animal breeding. A questionnaire-based survey from central Italy. (1st April 2021) - Pagliacci, Francesco; Luciani, Cristina; Russo, Margherita; Esposito, Fulvio; Habluetzel, Annette
Abstract: This paper investigates the socioeconomic impact of two large earthquakes (1997 and 2016) that occurred in Central Italy on the agricultural sector, and in particular on animal husbandry. Through a questionnaire-based field survey, involving 55 farm holdings located in Umbria (Assisano district), this work points out: i) the farmers' perception of the damage suffered with regard to residential buildings, agricultural facilities and animal husbandry activities; ii) the interventions carried out in the emergency phases; and iii) the reconstruction phases, as experienced by the farming households. Major vulnerabilities of these agricultural holdings have emerged: small-scale family-based farming, increased householders average age, little on-farm and off-farm diversification, persisting economic marginalisation. Recall and perception of the impact of the earthquakes in the Assisano district - direct damage and reconstruction interventions - are compared with the perception in the nearby mountainous area of the Marche Region, largely affected by the 2016 earthquake. In both areas, the experienced earthquakes have not acted as triggers for agents' mobilisation and change. Rather, the situation calls for a drastic, farsighted change of development policies by national and regional governments and for a convinced prompting for holistic local "building back better" initiatives.